Model based fault detection in process plant - Leong, Wah Heng; Ahmad, Arshad (1997)
In this paper, the application of neural network in detecting sensor failures is presented. The study was conducted on the Tennessee Eastman test problem. Faulty conditions were generated by imposing sensor failures in the reactor operation. Both single and multiple fault conditions were investigated. The results revealed that a three layer feedforward network was capable of providing the intended function.